CD8+ T Cells Promote Pathological Angiogenesis in Ocular Neovascular Disease. Issue 4 (16th February 2023) - Deliyanti, Devy; Figgett, William A.; Gebhardt, Thomas; Trapani, Joseph A.; Mackay, Fabienne; Wilkinson-Berka, Jennifer L.
Abstract : Background: CD4 + (cluster of differentation) and CD8 + T cells are increased in the ocular fluids of patients with neovascular retinopathy, yet their role in the disease process is unknown. Methods: We describe how CD8 + T cells migrate into the retina and contribute to pathological angiogenesis by releasing cytokines and cytotoxic factors. Results: In oxygen-induced retinopathy, flow cytometry revealed the numbers of CD4 + and CD8 + T cells were increased in blood, lymphoid organs, and retina throughout the development of neovascular retinopathy. Interestingly, the depletion of CD8 + T cells but not CD4 + T cells reduced retinal neovascularization and vascular leakage. Using reporter mice expressing gfp (green fluorescence protein) in CD8 + T cells, these cells were localized near neovascular tufts in the retina, confirming that CD8 + T cells contribute to the disease. Furthermore, the adoptive transfer of CD8 + T cells deficient in TNF (tumor necrosis factor), IFNγ (interferon gamma), Prf (perforin), or GzmA/B (granzymes A/B) into immunocompetent Rag1 −/− mice revealed that CD8 + T cells mediate retinal vascular disease via these factors, with TNF influencing all aspects of vascular pathology. The pathway by which CD8 + T cells migrate into the retina was identified as CXCR3 (C-X-C motif chemokine receptor 3) with the CXCR3 blockade reducing the number of CD8 + T cells within the retina and retinal vascular disease. Conclusions: We discovered that CXCR3 is central to the migration of CD8 + T cells into the retina as the CXCR3 blockade reduced the number of CD8 + T cells within the retina and vasculopathy. This research identified an unappreciated role for CD8 + T cells in retinal inflammation and vascular disease. Reducing CD8 + T cells via their inflammatory and recruitment pathways is a potential treatment for neovascular retinopathies.